‘Practice what you preach’. Perspectives on the involvement of people with dementia and carers in community-based dementia friendly initiatives, a qualitative study - Thijssen, Marjolein; Dauwerse, Linda; Lemmers, Frans; Sanden, Maria Nijhuis-van der; Daniels, Ramon; Graff, Maud; Kuijer-Siebelink, Wietske (Frontiers in Psychiatry, 2024)
People with dementia and their carers experience social stigma and often refrain from social participation. Significant improvement might be achieved by creating Dementia Friendly communities (DFCs) for which dementia friendly initiatives (DFIs) are needed. DFIs are developed by a variation of stakeholders. However, people with dementia and their carers are often unrepresented herein. This study aims to get insight into the perspectives of stakeholders (e.g., health-and social care professionals, volunteers, people with dementia and their carers) about the involvement of people with dementia and their carers during the development and sustainment of DFIs.Descriptive qualitative study, using a co-research design with a carer as co-researcher.Nineteen semi-structured interviews with stakeholders, including people with dementia and their carers, were performed. Inductive content analysis took place using Atlas Ti.Four themes were found: 1) the involvement of people with dementia and their carers is important for both people with dementia and their carers and other stakeholders; 2) personal character traits, life histories, and associated emotions evoke the need for involvement; 3) involvement requires an open, responsive stance and building relationships; and 4) the estimation of one's own and others' capacities influences perspectives on involvement. As such, practice what you preach means actively adopting an open, responsive approach and acknowledging the unique abilities and backgrounds of people with dementia and their carers. It emphasizes the importance of actually living by the values you advocate for.Central to perspectives on involving people with dementia and their carers is the emphasis on working relationally, differing from service-led and pre-structured patient and public involvement (PPI). Working relationally calls for organizational shifts aligned with a rightsbased perspective to avoid tokenism, and promotion of user-led organizations with genuine partnerships. Creative methods, problem-solving, and communication skills are essential for the development and sustainment of inclusive, supportive, person-centered DFIs. Future studies should explore the long-term impact of the involvement and working relationally on the well-being of people with dementia and their carers.